Olympic preparation of a world-class female triathlete - Mujika, I. (International Journal of Sports Physiology and Performance, 2014)
Detailed accounts of the training programs followed by today`s elite triathletes are lacking in the sport-science literature. This study reports on the training program of a world-class female triathlete preparing to compete in the London 2012 Olympic Games. Over 50 wk, she performed 796 sessions (303 swim, 194 bike, 254 run, 45 strength training), ie, 16 ± 4 sessions/wk (mean ± SD). Swim, bike, and run training volumes were, respectively, 1230 km (25 ± 8 km/wk), 427 h (9 ± 3 h/wk), and 250 h (5 ± 2 h/wk). Training tasks were categorized and prescribed based on heart-rate values and/or speeds and power outputs associated with different blood lactate concentrations. Training performed at intensities below her individual lactate threshold (ILT), between the ILT and the onset of blood lactate accumulation (OBLA), and above the OBLA for swim were 74% ± 6%, 16% ± 2%, 10% ± 2%; bike 88% ± 3%, 10% ± 1%, 2.1% ± 0.2%; and run 85% ± 2%, 8.0% ± 0.3%, 6.7% ± 0.3%. Training organization was adapted to the busy competition calendar (18 events, of which 8 were Olympic-distance triathlons) and continuously responded to emerging information. Training volumes were 35-80% higher than those previously reported for elite male and female triathletes, but training intensity and tapering strategies successfully followed recommended best practice for endurance athletes. This triathlete placed 7th in London 2012, and her world ranking improved from 14th to 8th at the end of 2012.